Designing and Manufacturing a Vacuum Frying System with Intelligent Controlling - Chau, Thanh Tuan; Do, Thuy Khanh Linh; Nguyen, Tan Dung (Journal of Technical Education Science, 2023)
Vacuum frying is one of the advanced technologies for food processing to make high-quality fried products by decreasing smoked temperature of oil. In this study, the vacuum frying system was calculated, designed, and manufactured using potato slices as material. The system was successfully manufactured using shortening as the frying oil and the optimal frying conditions were 105ºC, 150 mmHg for 10 minutes. The frying process was automatically controlled and measured by computer-programmed software. The system consists of a heat power (6.33 kW), a cylinder frying tank (400 mm diameter × 750 mm height), a vacuum pump (0.75 kW, a condensing equipment (0.45 kW, 30mm diameter × 440 mm length), and a freezing compressor (1.12 kW). The frying capacity of the system is 24 kg material for 4 hours, consisting of 12 frequencies (20 minutes of frying time for 2 kg material for each). After manufacturing, the system was used for frying potatoes to test and assess the effectiveness and adjust the optimal conditions. The fried potato indicated the required moisture, suitable quality, typical color and taste, and low energy costs. This result can help to master vacuum frying manufacturing technology for domestic engineering.